Effects of Culture Conditions on Growth and Cyclooligomer Depsipeptides Biosynthesis of Cordyceps sp. CPA14V - Thi Thuy Van, Nguyen; Viet, Nguyen Dinh; Lam, Duong Minh (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 1, 2021)
Cordyceps sp. CPA14V was isolated from insect-fungi sample that was collected from Copia - Son La Nature Reserve. The strain was able to biosynthesize cyclooligomer depsipeptides (CODs). This study aimed to identify Cordyceps sp. CPA14V to species using DNA sequence analysis and to estimate the effects of carbon, nitrogen, pH of culture broth on its growth and COD producing capacity. The results showed that the studied strain was Cordyceps cateniannulata CPA14V. This is the first record of the species in Vietnam. Glucose, yeast extract and pH=8.0 were the most suitable for growth and CODs synthesis of C. cateniannulata CPA14V. This is also the first report of CODs produced by a C. cateniannulata .